Detection of a novel Pestivirus strain in Java ticks (Amblyomma javanense) and the hosts Malayan pangolin (Manis javanica) and Chinese pangolin (Manis pentadactyla) - Shi, Yuan-Ni; Li, Lin-Miao; Zhou, Jia-Bin; Hua, Yan; Zeng, Zhi-Liao; Yu, Ye-Pin; Liu, Ping; Yuan, Zi-Guo; Chen, Jin-Ping (Frontiers in Microbiology, 2022)
Pangolins are endangered animals and are listed in the CITES Appendix I of the International Trade Protection List of Wild Fauna and Flora and the national first-level protected wild animal in China. Based on few reports on pangolins infected with pestiviruses of the Flaviviridae family, Pestivirus infections in pangolins have attracted increasing attention. Pestivirus is a pathogen that is usually transmitted by the tick Amblyomma javanense that can cause diseases such as acute diarrhea and acute hemorrhagic syndrome. To better understand the epidemiology and genomic characterization of pestiviruses carried by pangolins, we detected pestiviruses in dead Malay pangolins using metavirome sequencing technology and obtained a Pestivirus sequence of 11,579 nucleotides (named Guangdong pangolin Pestivirus, GDPV). Phylogenetic tree analysis based on the entire coding sequence, and NS3 protein and RdRp gene sequences showed that GDPV was closely related to previously reported pangolin-derived Pestivirus and clustered into a separate branch. Molecular epidemiological investigation revealed that 36 pangolins (a total of 144 tissues) and 31 A. javanense ticks carried pestiviruses. There were 15 Pestivirus-positive pangolin individuals with a positivity rate of 10.42%, and 6 A. javanense carried pestiviruses with a positivity rate of 19.35%. Moreover, the RdRp gene of the Pestivirus carried by A. javanense showed a high similarity to that carried by pangolins (93-100%), indicating A. javanense is likely to represent the vector of Pestivirus transmission. This study expands the diversity of viruses carried by pangolins and provides an important reference value for interrupting the transmission route of the virus, thereby protecting the health of pangolins.